NCOR1—a new player on the field of T cell development. Issue 6 (17th August 2018) - Müller, Lena; Hainberger, Daniela; Stolz, Valentina; Ellmeier, Wilfried
Abstract: Nuclear receptor corepressor 1 (NCOR1) is a transcriptional corepressor that links chromatin-modifying enzymes with gene-specific transcription factors. Although identified more than 20 years ago as a corepressor of nuclear receptors, the role of NCOR1 in T cells remained only poorly understood. However, recent studies indicate that the survival of developing thymocytes is regulated by NCOR1, revealing an essential role for NCOR1 in the T cell lineage. In this review, we will briefly summarize basic facts about NCOR1 structure and functions. We will further summarize studies demonstrating an essential role for NCOR1 in controlling positive and negative selection of thymocytes during T cell development. Finally, we will discuss similarities and differences between the phenotypes of mice with a T cell-specific deletion of NCOR1 or histone deacetylase 3 (HDAC3), because HDAC3 is the predominant member of the HDAC family that interacts with NCOR1 corepressor complexes. With this review we aim to introduce NCOR1 as a new player in the team of transcriptional coregulators that control T cell development and thus the generation of the peripheral T cell pool. Review on the role of the transcriptional corepressor NCOR1 during T cell development.